Management of unpredictable outcomes of costochondral grafts. (2019) - Sekhoto, Mmathabo G.; Rikhotso, Risimati E.; Rajendran, Sumetha
Highlights: TMJ ankylosis is a debilitating mandibular hypomobility disorder. CCGs are generally considered as the gold standard for autogenous reconstruction of mandibular condyle. Total alloplastic TMJ prosthesis is a viable option in the case of undesirable outcomes from CCGs. Management of TMJ ankylosis in children is dependent on aggressive physiotherapy, and long-term follow-up. Abstract: Introduction: Temporomandibular joint (TMJ) ankylosis is a debilitating mandibular hypomobility disorder that may be associated with serious functional and aesthetic deformities including limited mouth opening, impaired mastication and disturbances of facial and mandibular growth. The ultimate treatment goal of TMJ ankylosis is to restore altered joint mechanics, correct associated dentofacial deformities and prevent reankylosis. Presentation of case: We present a case of a 16 year old patient who returned with excessive mandibular growth and TMJ reankylosis following treatment of TMJ ankylosis with CCGs when he was 8 years old. Discussion: Various treatment modalities for TMJ ankylosis have been described. These include gap arthroplasty (GAP), interpositional gap arthroplasty (IPG) and/or total joint reconstruction (with autogenous costochondral grafts or alloplastic materials), and distraction osteogenesis. Costochondral grafts (CCGs) are generally preferred for the treatment of TMJ ankylosis, especially in the growing patient. Their advantages include biocompatibility, no financial cost to the patient, low donor site morbidity, and most importantly their potential for mandibular growth. The growth of the mandible is however unpredictable. Conclusion: The optimal surgical management of this complex patient with combined orthognathic surgery and total alloplastic joint reconstruction is discussed.